Crystallization and preliminary X‐ray characterization of the 2, 4′‐dihydroxyacetophenone dioxygenase from Alcaligenes sp. 4HAP. Issue 6 (1st June 2014) - Beaven, G.; Bowyer, A.; Erskine, P.; Wood, S. P.; McCoy, A.; Coates, L.; Keegan, R.; Lebedev, A.; Hopper, D. J.; Kaderbhai, M. A.; Cooper, J. B.
<x xml:space="preserve">Abstract</x> The enzyme 2, 4′‐dihydroxyacetophenone dioxygenase (or DAD) catalyses the conversion of 2, 4′‐dihydroxyacetophenone to 4‐hydroxybenzoic acid and formic acid with the incorporation of molecular oxygen. Whilst the vast majority of dioxygenases cleave within the aromatic ring of the substrate, DAD is very unusual in that it is involved in C—C bond cleavage in a substituent of the aromatic ring. There is evidence that the enzyme is a homotetramer of 20.3 kDa subunits each containing nonhaem iron and its sequence suggests that it belongs to the cupin family of dioxygenases. By the use of limited chymotrypsinolysis, the DAD enzyme from Alcaligenes sp. 4HAP has been crystallized in a form that diffracts synchrotron radiation to a resolution of 2.2 Å.